Romance and Femininities in Indonesian Teenage Dramas: A Transnational Post-Feminist Analysis - Rahmawati, Aulia (Jurnal Perempuan, 2018)
Even after the rise of Indonesian feminist film directors by the likes of Nia Dinata, Mira Lesmana, Mouly Surya, Nan T Achnas and Lola Amaria, the Indonesian moviegoers still flocked into badly written teenage romance dramas. This paper interrogates the way romance and femininities have been shaped within the cinematic representation in London Love Story 2, Promise and Dear Nathan. It is concluded that the Indonesian romance teenage dramas are entrenched with masculine power and dominance spectacles in which the feminine heroines have been treated as passive objects of desire whose agency and subjectivities are being stripped away. Using feminist literature on post-feminist romance cinema, the heroines in these films have mostly been constructed as independent, smart and seemingly agentive at first, but nevertheless pursued romantic, traditional, heterosexual relationships saturated with masculinecontrol and dominance. This paper shows that post-feminist popular culture has transpired globally and morphed into transnational post-feminism that influenced the production and consumption of such text in Indonesia.